2020
DOI: 10.1016/j.eats.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Precise Arthroscopic Mini-trochleoplasty and Medial Patellofemoral Ligament Reconstruction for Recurrent Patellar Instability With Severe Trochlear Dysplasia

Abstract: More than 100 surgical procedures have been reported to address recurrent patellar instability. Trochlear dysplasia is the most common finding among the anatomic risk factors for recurrent patellar instability. Various studies have shown that trochleoplasty combined with medial patellofemoral ligament reconstruction is an effective technique to treat recurrent patellar instability. Nevertheless, trochleoplasty is still a daunting procedure for surgeons because of its multiple and gloomy complications. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…Trochlear dysplasia exists on a spectrum, resulting in an array of surgical options from minimally invasive arthroscopic bumpectomy 21 to various methods of trochleoplasty. 10 , 12 , 13 , 14 , 15 , 22 For patients with grade B and D trochlear dysplasia with a supratrochlear spur, evidence has shown that sulcus deepening trochleoplasty can improve patellofemoral stability, 17 , 23 although patients tend to also have congruent dysplasia that likewise affects the patella. 24 At a mean of 15 years’ follow-up, Rouanet et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trochlear dysplasia exists on a spectrum, resulting in an array of surgical options from minimally invasive arthroscopic bumpectomy 21 to various methods of trochleoplasty. 10 , 12 , 13 , 14 , 15 , 22 For patients with grade B and D trochlear dysplasia with a supratrochlear spur, evidence has shown that sulcus deepening trochleoplasty can improve patellofemoral stability, 17 , 23 although patients tend to also have congruent dysplasia that likewise affects the patella. 24 At a mean of 15 years’ follow-up, Rouanet et al.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Trochleoplasty has historically been indicated in cases of objective patellar instability associated with high-grade (grade B or D) dysplasia or recurrent instability after previous surgery. 10 Several trochlear deepening techniques have been described, 11 , 12 , 13 , 14 , 15 with Duncan et al. 16 succinctly summarizing many of them.…”
mentioning
confidence: 99%
“…Blønd and Schottle described an arthroscopic thin‐flap trochleoplasty through multiple superior portals with the use of a motorized shaver and resorbable sutures and anchors [8]. This technique, which has been further modified, is very promising for decreasing invasivity and improving clinical results but still need medium and long‐term follow‐up confirmation [50].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Aktuell ist die Methode nach Bereiter weit verbreitet, die von uns bevorzugt und im Weiteren näher beschrieben wird 4 . Des Weiteren existieren auch arthroskopische Verfahren, um die Invasivität zu minimieren 5 18 .…”
Section: Die Trochleaplastikunclassified